Exact travelling wave solutions of the symmetric regularized long wave (SRLW) using analytical methods - Manafian Heris, Jalil; Zamanpour, Isa (Statistics, Optimization & Information Computing, 2014)
In this article, we establish exact travelling wave solutions of the symmetric regularized long wave (SRLW) by using analytical methods. The analytical methods are: the tanh-coth method and the sech^2 method which used to construct solitary wave solutions of nonlinear evolution equations. With the help of symbolic computation, we show that aforementioned methods provide a straightforward and powerful mathematical tool for solving nonlinear partial differential equations.